Enhancing Green Cover in Andhra Pradesh - Khajuria, Rajendra Prasad (Indian Forester, 2020)
National Forest Policy (NFP), 1988 of the Government of India prescribes that minimum 33% of the total land area should be brought under forest and tree cover in plains. The state of Andhra Pradesh so far has been able to achieve 19.57% forest and tree cover, which is well below the mandated 33% goal. This study discusses in detail how the state of Andhra Pradesh can make strategies to enhance its forest and tree cover to the national goal of 33%. Forest Survey of India data from the State of Forests Reports is used to analyse the forest and tree cover data at the district level. It is observed that the state can achieve maximum 22.83% forest cover commensurate with its recorded forest area. Balance 10.17% green cover has to be met from the Trees outside forests (TOF). The land use pattern in the state reveals that TOF can be raised under agroforestry and in barren and wastelands. Getting the area from other land uses may not be possible. About 8 lakh ha may have to be brought under agroforestry and another 5 lakh ha under barren and wastelands in the long-term, say about 10 years to achieve the desired results. Various issues in agroforestry have been flagged and the mechanisms to address them especially through the National Agroforestry Policy, 2014 are also discussed. These are huge targets and need focused approach, proper planning and funding tie-ups. The study concludes with additional benefits under REDD+ when the national goal under NFP, 1988 is met.